Targeting of GFP-Cre to the mouse Cyp11a1 locus both drives cre recombinase expression in steroidogenic cells and permits generation of Cyp11a1 knock out mice. - Laura O'Hara; Jean Philippe York; Pumin Zhang; Lee B Smith (PLoS ONE)
To permit conditional gene targeting of floxed alleles in steroidogenic cell-types we have generated a transgenic mouse line that expresses Cre Recombinase under the regulation of the endogenous Cytochrome P450 side chain cleavage enzyme (Cyp11a1) promoter. Mice Carrying the Cyp11a1-GC (GFP-Cre) allele express Cre Recombinase in fetal adrenal and testis, and adrenal cortex, testicular Leydig cells (and a small proportion of Sertoli cells), theca cells of the ovary, and the hindbrain in postnatal life. Circulating testosterone concentration is unchanged in Cyp11(+/GC) males, suggesting steroidogenesis is unaffected by loss of one allele of Cyp11a1, mice are grossly normal, and Cre Recombinase functions to recombine floxed alleles of both a YFP reporter gene and the Androgen Receptor (AR) in steroidogenic cells of the testis, ovary, adrenal and hindbrain. Additionally, when bred to homozygosity (Cyp11a1(GC/GC) ), knock-in of GFP-Cre to the endogenous Cyp11a1 locus results in a novel mouse model lacking endogenous Cyp11a1 (P450-SCC) function. This unique dual-purpose model has utility both for those wishing to conditionally target genes within steroidogenic cell types and for studies requiring mice lacking endogenous steroid hormone production.